2008
DOI: 10.1111/j.1365-3040.2008.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultraviolet radiation, photosensitizers, reactive oxygen species and ester groups in mechanisms of methane formation from pectin

Abstract: Ultraviolet (UV) radiation has recently been demonstrated to drive an aerobic production of methane (CH4) from plant tissues and pectins, as do agents that generate reactive oxygen species (ROS) in vivo independently of UV. As the major building-blocks of pectin do not absorb solar UV found at the earth's surface (i.e. >280 nm), we explored the hypothesis that UV radiation affects pectin indirectly via generation of ROS which themselves release CH4 from pectin. Decreasing the UV absorbance of commercial pectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
134
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 51 publications
2
134
0
1
Order By: Relevance
“…However, the response of plants and their components to ROS yields many products and might enable CH 4 generation (Apel and Hirt, 2004;Moller et al, 2007). The observation that CH 4 emissions were significantly stimulated by ROS generators and constrained by ROS scavengers also implies the importance of ROS in plant CH 4 formation (Messenger et al, 2009). The disturbance of the electron transport chain (ETC) in plant cells can occur under stress conditions (Moller et al, 2007).…”
Section: Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the response of plants and their components to ROS yields many products and might enable CH 4 generation (Apel and Hirt, 2004;Moller et al, 2007). The observation that CH 4 emissions were significantly stimulated by ROS generators and constrained by ROS scavengers also implies the importance of ROS in plant CH 4 formation (Messenger et al, 2009). The disturbance of the electron transport chain (ETC) in plant cells can occur under stress conditions (Moller et al, 2007).…”
Section: Plantsmentioning
confidence: 99%
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that CH 4 can be produced abiotically from plant material by exposing it to ultraviolet (UV) irradiation [15][16][17][18] . A reaction of reactive oxygen species (ROS) with methoxyl groups of pectic polysaccharides was suggested as a possible route to CH 4 formation under UV radiation 19 . On the other hand, several recent studies 2,9,10 , using 13 C-labelled plant and fungal species, have demonstrated that there is also continuous formation of CH 4 in living plants and fungi without any microbial contribution.…”
mentioning
confidence: 99%